North American natural gas market and infrastructure developments under different mechanisms of renewable policy coordination. (January 2021) - Avraam, Charalampos; Bistline, John E.T.; Brown, Maxwell; Vaillancourt, Kathleen; Siddiqui, Sauleh
Abstract: Renewable Portfolio Standards (RPS) accelerate renewables deployment but their impact on fuel-fired plants remains ambiguous. North American natural gas consumption has been growing due to its decreasing cost in North America, policy initiatives, and its relatively low CO2 emissions rate compared to coal. In this paper, we study the implications for the natural gas sector of more stringent RPS under different coordination schemes in an integrated North American natural gas market. The scenarios assume that Renewable Energy Certificates generated in each region are traded 1) among all countries, 2) only within each country, and 3) only within model regions. We implement the three policies in four different energy and electricity models to generate projections of future natural gas consumption. Subsequently, we feed regional or country-level consumption changes of each model in each scenario to the North American Natural Gas Model. We find that lower RPS coordination among regions results in increased U.S. natural gas exports to Canada, increased U.S. natural gas prices, and decreased net U.S. natural gas exports to Mexico in the long term. Moreover, international coordination of RPS in the electricity sector leads to smaller price discrepancies in the U.S. natural gas market when compared to the reference scenario. Highlights: Assess the impact of renewable policy coordination on natural gas infrastructure. Sensitivity analysis of natural gas markets using linked inputs from four different models. Coordination of renewable policies can mitigate the impact on natural gas markets. Renewable policy can affect natural gas prices less with higher policy coordination. Lower renewable policy coordination can increase U.S. natural gas exports to Canada.